Preliminary Survey of the Spider Fauna of Great Inagua, Bahamas, W.I. - Sewlal, Jo-Anne Nina; Starr, Christopher K. (International Journal of Bahamian Studies, 2011)
During a 10-day period between December 2010 and January 2011, a variety of habitats on the island of Great Inagua, Bahamas, West Indies, were surveyed for the presence of spiders. Sampling efforts produced roughly equal species richness in both natural habitats and those that were man made or altered by human activity. Members of the families Araneidae and Tetragnathidae comprised almost half of the species found. Five localities were surveyed from six habitats, including three altered and three natural. Twenty-five species representing ten families were collected.